The Pseudomonas putida CsrA/RsmA homologues negatively affect c‐di‐GMP pools and biofilm formation through the GGDEF/EAL response regulator CfcR. (21st July 2017) - Huertas‐Rosales, Óscar; Romero, Manuel; Heeb, Stephan; Espinosa‐Urgel, Manuel; Cámara, Miguel; Ramos‐González, María Isabel
Summary: Expression of cfcR, encoding the only GGDEF/EAL response regulator in Pseudomonas putida, is transcriptionally regulated by RpoS, ANR and FleQ, and the functionality of CfcR as a diguanylate cyclase requires the multisensor CHASE3/GAF hybrid histidine kinase named CfcA. Here an additional level of cfcR control, operating post‐transcriptionally via the RNA‐binding proteins RsmA, RsmE and RsmI, is unraveled. Specific binding of the three proteins to an Rsm‐binding motif (5′CANGGANG3′) encompassing the translational start codon of cfcR was confirmed. Although RsmA exhibited the highest binding affinity to the cfcR transcript, single deletions of rsmA, rsmE or rsmI caused minor derepression in CfcR translation compared to a ΔrsmIEA triple mutant. RsmA also showed a negative impact on c‐di‐GMP levels in a double mutant ΔrsmIE through the control of cfcR, which is responsible for most of the free c‐di‐GMP during stationary phase in static conditions. In addition, a CfcR‐dependent c‐di‐GMP boost was observed during this stage in ΔrsmIEA confirming the negative effect of Rsm proteins on CfcR translation and explaining the increased biofilm formation in this mutant compared to the wild type. Overall, these results suggest that CfcR is a key player in biofilm formation regulation by the Rsm proteins in P. putida .